2010
DOI: 10.1038/aps.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of rhTNFR-Fc in healthy Chinese volunteers and in Chinese patients with Ankylosing spondylitis

Abstract: Aim:To investigate the population pharmacokinetics of recombinant human tumor necrosis factor receptor-Fc fusion protein (rhTNFRFc) administered via subcutaneous (SC) injection in healthy Chinese volunteers and in Chinese patients with ankylosing spondylitis (AS). Methods: Thirty-two healthy volunteers were randomly assigned to receive a single SC injection of 12.5, 25, 37.5, or 50 mg of rhTNFRFc. Twenty male patients with moderate AS were randomly assigned to receive seven consecutive SC injections of rhTNFR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…It is worth noting that sex significantly affected the PK profile of rhTNFR:Fc in the Chinese population, the apparent clearance of men was 0.665 times as high as that of women. 19 Similar results were also reported in the American population: The apparent clearance of men was higher than that of women in patients with RA, although this difference did not reach statistical significance. 20,21 Currently, whether the dosage of rhTNFR:Fc should be adjusted based on sex difference is unclear and should be investigated in larger trials.…”
Section: Discussionsupporting
confidence: 72%
“…It is worth noting that sex significantly affected the PK profile of rhTNFR:Fc in the Chinese population, the apparent clearance of men was 0.665 times as high as that of women. 19 Similar results were also reported in the American population: The apparent clearance of men was higher than that of women in patients with RA, although this difference did not reach statistical significance. 20,21 Currently, whether the dosage of rhTNFR:Fc should be adjusted based on sex difference is unclear and should be investigated in larger trials.…”
Section: Discussionsupporting
confidence: 72%
“…However, a general trend for underprediction of t max was observed when using the PBPK model. Lag times of up to 3 h have been included in other models of TP SC absorption to describe the time delay between dose and recovery in central lymph (14,36,45,7678). Similarly, the radiolabelled IgG data used for model development showed a lag of ~0.5 h between dosing and loss of IgG from the dose site (2830).…”
Section: Discussionmentioning
confidence: 99%
“…[11,[18][19][20][21] In addition, a previous population-based pharmacokinetic study of etanercept indicated that the pharmacokinetics in rheumatoid arthritis and ankylosing spondylitis patients is similar to that in healthy volunteers. [22][23][24] Therefore, reconstituted lyophilized (25 mg mL) HD203 and Enbrel Ò can be expected to result in similar pharmacokinetics in the clinical setting. However, due to the absence of pharmacodynamic markers for etanercept in healthy subjects, a comparative pharmacodynamic or efficacy trial of HD203 in a large number of patients will be required to demonstrate comparability.…”
Section: Discussionmentioning
confidence: 99%